Are there pre-programme effects of Swedish active labour market policies? Evidence from three randomised experiments - Pathric Hägglund (Institute for Labour Market Policy Evaluation (IFAU), 2006)
In this paper experimental data from three Swedish demonstration programmes in 2004 are used to study pre-programme effects of active placement efforts. In one of the experiments, targeted towards a broad group of UI receivers, arranged job-search activities in groups combined with increased monitoring of job-search efforts generated a 46 per cent increase in the escape rate between referral to and start of the programme services. This translates into a two-week reduction of the ongoing UI spell. Referrals to increased monitoring alone did not have the same effect on exit behaviour. In the other two experiments, targeted towards youth and highly educated respectively, referrals to active placement efforts had no effect on the pre-programme outflow.
Keywords: C93; J64; 330; Pre-programme effect; policy evaluation; social experiment; Arbeitsmarktpolitik; Wirkungsanalyse; Empirische Methode; Schweden